ENTEROSORBENTS AS A PART OF COMPLEX THERAPY OF ATOPIC DERMATITIS - A. A. Alexeeva (Вопросы современной педиатрии, 2012)
Atopic dermatitis (AD) is one of the most common allergic diseases in children which is assuming ever greater medical and social importance. Risk factors of AD include gastro-intestinal tract disturbances, especially intestinal dysbiosis, which is revealed in 89–94,1% of children with atopic dermatitis. Both correlation of the dysbiosis and AD manifestations severity and increase of underlying disease treatment efficacy as a result of target influence on intestinal microflora confirm that. For many decades guidelines of atopic dermatitis treatment in children along with elimination diet, antihistamine drugs and topic medicines include enterosorbents. The most effective drugs are those ones, consisting of prebiotics and sorbents. The wide experience of prebiotic drug with sorbent action (Lactofiltrum) in complex therapy of atopic dermatitis in children is reviewed in this article.